Evolving food systems in Ethiopia: Past, present and future - Minten, Bart; Dereje, Mekdim; Bachewe, Fantu Nisrane; Tamru, Seneshaw (International Food Policy Research Institute, 2018)
Ethiopia’s food systems are rapidly evolving, being driven by major contextual changes including high population growth, rapid urbanization, infrastructure investments, and income growth. These changes are illustrated by dietary, agricultural, and supply chain transformations. These transformations in Ethiopia’s food systems are expected to continue at a rapid pace given similar even more pronounced changes going forward. We expect to see especially rapid growth in commercial food markets. This will have enormous implications on farming and on the required development of efficient private-led agricultural input supply, logistics, trading, and distribution sectors.